Online vs offline arbitration in the field of resolving commercial disputes [Articol] - Voloshchyuk, Victoria; Kiriiak, Oksana (CEP USM, 2024)
In the article author declared that in the digital era, the digitization of civil-law relations and institutions, among which arbitration occupies an important place as an effective way of resolving commercial disputes, is an objective process that will simplify procedures and save time and funds. Obviously, online proceedings, hearings and meetings will not replace the offline format, but they have every chance to become an even better addition to the arsenal of official communication in the field of resolving commercial disputes between foreign partners. Also it is pointed that In the context of globalization of the modern world, commercialization and convergence of legal systems, businessmen who do business in different regions of the world are looking for new more mobile and effective means to resolve disputes, which would allow not only to save time, but also to qualitatively resolve the dispute on acceptable terms for both parties. It has long been necessary to recognize that international commercial arbitration is such a means. It is this alternative means of resolving commercial disputes, which is permeated with the principle of autonomy of the will of the parties, gives broad opportunities for the parties to choose the place of arbitration, language, rights on the basis of which the dispute will be resolved, as well as the arbitrators themselves. Undoubtedly, such opportunities place arbitration in a more favorable position in relation to the state court, where the parties must be aware of the law of the forum, speak the language of the proceedings and follow the clearly procedural rules of the state of the dispute.
Keywords: digitalization; arbitration; commercial disputes; online arbitration; offline arbitration